Age-related decrements in dual-task performance: Comparison of different mobility and cognitive tasks. A cross sectional study. - Paolo Riccardo Brustio; Daniele Magistro; Massimiliano Zecca; Emanuela Rabaglietti; Monica Emma Liubicich (PLoS ONE, 2017)
This cross-sectional study investigated the age-related differences in dual-task performance both in mobility and cognitive tasks and the additive dual-task costs in a sample of older, middle-aged and young adults. 74 older adults (M = 72.63±5.57 years), 58 middle-aged adults (M = 46.69±4.68 years) and 63 young adults (M = 25.34±3.00 years) participated in the study. Participants performed different mobility and subtraction tasks under both single- and dual-task conditions. Linear regressions, repeated-measures and one-way analyses of covariance were used, The results showed: significant effects of the age on the dual and mobility tasks (p<0.05) and differences among the age-groups in the combined dual-task costs (p<0.05); significant decreases in mobility performance under dual-task conditions in all groups (p<0.05) and a decrease in cognitive performance in the older group (p<0.05). Dual-task activity affected mobility and cognitive performance, especially in older adults who showed a higher dual-task cost, suggesting that dual-tasks activities are affected by the age and consequently also mobility and cognitive tasks are negatively influenced.